Effects of protocol step length on biomechanical measures in swimming - Barbosa, T. M.; de Jesus, K.; Abraldes, J. A.; Ribeiro, J.; Figueiredo, P.; Vilas-Boas, J. P.; Fernandes, R. J. (International Journal of Sports Physiology and Performance, 2015)
Background: The assessment of energetic and mechanical parameters in swimming often requires the use of an intermittent incremental protocol, whose step lengths are corner stones for the efficiency of the evaluation procedures. Purpose: To analyze changes in swimming kinematics and interlimb coordination behavior in 3 variants, with different step lengths, of an intermittent incremental protocol. Methods: Twenty-two male swimmers performed n × di variants of an intermittent and incremental protocol (n = 7; d1 = 200 m, d2 = 300 m, and d3 = 400 m). Swimmers were videotaped in the sagittal plane for 2-dimensional kinematical analysis using a dual-media setup. Video images were digitized with a motion-capture system. Parameters that were assessed included the stroke kinematics, the segmental and anatomical landmark kinematics, and interlimb coordination. Movement efficiency was also estimated. Results: There were no significant variations in any of the selected variables according to the step lengths. A high to very high relationship was observed between step lengths. The bias was much reduced and the 95%CI fairly tight. Conclusions: Since there were no meaningful differences between the 3 protocol variants, the 1 with shortest step length (ie, 200 m) should be adopted for logistical reasons.